Origin and Ideological Moorings of Hamas: The Origins, Ideology, and Goals of Hamas (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Hamas an acronym for an original Arabic name Harkat al-Mokwama al-Islamiya, which means ‘Zeal’ was officially founded on 14 December 1987 but its origins can be traced back to the Egyptian Muslim Brotherhood which was founded by a school teacher Hassan al-Banna in 1928. Sheikh Ahmad Yassin, who has been considered as the founder of Hamas was active in Palestinian politics since 1970s. Greatly influenced by the ideas and teachings of the Muslim Brotherhood, Sheikh Ahmad Yassin formed an Islamic Society in 1976. By 1978, he felt the need for a bigger and better organization to promote Islamic values in the Palestinian society. This thought led him to establish Islamic Compound. However, Maktura incident of Jabaliya refugee camp was an immediate cause for the formation of Hamas.Hamas adopted its Charter on 18 August 1988, which contains its basic ideological commitments and proclaims its goal, means for the realization of goal and Hamas’ world view. Hamas clearly states that it derives its ideology from Islam and its goal is to liberate all of historic Palestine. This paper is an attempt to discover the origin, roots and the role of Sheikh Ahmad Yassin in founding Hamas, and tracing the ideological moorings of Hamas along with its bases. It also aims to find the perception of Hamas on the Jews, Judaism, Zionism, Western countries and ultimately the goal of Hamas.